FREQUENCY OF CONGESTIVE HEART FAILURE IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE PRESENTED TO TERTIARY CARE HOSPITAL (The Research of Medical Science Review, 2025)
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is a major contributor to global morbidity and mortality, particularly in individuals over 40 years of age. It is projected to become the fourth leading cause of premature death by 2040. In 2023, COPD was redefined as a heterogeneous lung condition characterized by persistent respiratory symptoms and airflow obstruction due to airway and/or alveolar abnormalities. Cardiovascular comorbidities, especially heart failure, are common in COPD patients but often under-recognized.OBJECTIVE: To determine the frequency of heart failure in patients with chronic obstructive pulmonary disease.METHODS: This cross-sectional study was conducted at the Department of Pulmonology, Lady Reading Hospital Peshawar. A total of 113 diagnosed COPD patients were enrolled through consecutive sampling. Data on demographics, clinical history, and comorbidities were collected. Heart failure was identified using standard clinical criteria and investigations. Associations between heart failure and patient variables were analyzed using the Chi-square test, with a p-value <0.05 considered statistically significant.RESULTS: Heart failure was present in 41.6% of COPD patients. Significant associations were observed between heart failure and age (p=0.021), gender (p=0.029), BMI (p=0.015), employment status (p=0.047), monthly income (p=0.031), socioeconomic status (p=0.019), educational level (p=0.038), duration of COPD (p=0.009), and smoking status (p=0.032).CONCLUSION: Heart failure is highly prevalent among COPD patients and is significantly linked with multiple demographic and clinical risk factors. Early identification and integrated care strategies are essential to improve outcomes and reduce the burden of comorbid conditions in this population.